Novel α-Tubulin Mutations Conferring Resistance to Dinitroaniline Herbicides in Lolium rigidum - Chu, Zhizhan; Chen, Jinyi; Nyporko, Alex; Han, Heping; Yu, Qin; Powles, Stephen (Frontiers in Plant Science, 2018)
Abstract The dinitroaniline herbicides (particularly trifluralin) have been globally used in many crops for selective grass weed control. Consequently, trifluralin resistance has been documented in several important crop weed species and has recently reached a level of concern in Australian Lolium rigidum populations. Here, we report novel mutations in the L. rigidum α-tubulin gene which confer resistance to trifluralin and other dinitroaniline herbicides. Nucleotide mutations at the highly conserved codon Arg-243 resulted in amino acid substitutions of Met or Lys. Rice calli transformed with the mutant 243-Met or 243-Lys α-tubulin genes were 4- to 8-fold more resistant to trifluralin and other dinitroaniline herbicides (e.g. ethalfluralin and pendimethalin) compared to calli transformed with the wild type -tubulin gene from L. rigidum. Comprehensive modelling of molecular docking predicts that Arg-243 is close to the trifluralin binding site on the α-tubulin surface and that replacement of Arg-243 by Met/Lys-243 results in a spatial shift of the trifluralin binding domain, reduction of trifluralin-tubulin contacts, and unfavourable interactions. The major effect of these substitutions is a significant rise of free interaction energy between α-tubulin and trifluralin, as well as between trifluralin and its whole molecular environment. These results demonstrate that the Arg-243 residue in α-tubulin is a determinant for trifluralin sensitivity, and the novel Arg-243-Met/Lys mutations may confer trifluralin resistance in L. rigidum.